FENOMENA PERCERAIAN DI MASA PANDEMI DI PENGADILAN AGAMA BEKASI - Rafi Anazli; Suprihatin Suprihatin; Oni Wastoni (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
Divorce is a painful thing for husbands and wives. In the Hadith narrated by Ibn Majah, it is said, "Divorce is a lawful thing but is hated by Allah SWT." Therefore, Islam views divorce as an emergency exit that is only taken if there is no solution. But in a pandemic situation, divorce can also occur, as stated in decision number 0345/Pdt.G/2021/PA.Bks and number 0138/Pdt.G/2021/PA.Bks This study aims to analyze the judge's decision to divorce during the pandemic at the Bekasi Religious Court in decision No. 0345/Pdt.G/2021/PA.Bks and No. 0138/Pdt.G/2021/PA.Bks, The researcher, used a mixed qualitative method, namely juridical normative and socio-legal research (field) with a qualitative approach; researchers conducted observations, documentation, and interviews. The sample in this study amounted to 2 respondents, with details such as two judges at the Bekasi Religious Court. The data sources were researched namely, primary and secondary legal materials. The study's results stated that the divorce phenomenon during the Covid-19 pandemic in decision no. 0345/Pdt.G/2021/PA.Bks and no. 0138/Pdt.G/2021/PA.Bks is an instinct to maintain happiness in life. This is permissible in Islamic law based on Malahat and Saddu Adz-Zariah.